The Biomechanical Effects of Sagittal Split Ramus Osteotomy on Temporomandibular Joint. Issue 11 (18th August 2018) - Liu, Zhan; Shu, Jingheng; Zhang, Yuanli; Fan, Yubo
Abstract: The aim of this study was to evaluate the stress distributions and deformations of the temporomandibular joint (TMJ) during different periods before and after sagittal split ramus osteotomy (SSRO). A three-dimensional finite element model of the mandible and TMJ was established, based on the preoperative CT of a patient with mandibular prognathism. Numerical SSRO was performed and the models of three postoperative periods were established. Contact elements were used to simulate the interaction between the articular discs and the articular cartilages. Nonlinear cable elements were used to simulate the disc attachments and the ligaments. Muscle forces and boundary conditions corresponding to the central occlusion were applied on all the models. The results showed that the stress distributions of the patient's TMJs were not the same as those of asymptomatic subjects. The stress distributions and deformations of the disc, condylar and temporal cartilage were changed at different periods after SSRO. The biomechanical parameters of TMJ were improved after SSRO. And the postoperative results showed that appropriate functional training could help to avoid TMJ diseases. Therefore SSRO could improve the stress distributions of the TMJ and relieve the symptoms of temporomandibular disorder (TMD).